Potential of Several Phytochemicals of Mangrove Species (Rhizopora stylosa) as Inhibitor of Both Viral Gene Expression and Bacterial Nucleic Acid Synthesis - Hadi, Ismanurrahman; Irawan, Ade; Ulfah, Mariam; Putra, Teguh Adiyas; Efriani, Like; Haq, Mailatul Ilal; Purnama, Muhamad Rifki (Universitas Muhammadiyah Kalimantan Timur, 2022)
The mangrove family (Rhizophora stylosa) has been used as traditional medicine. Due to the habitat of mangroves, they develop unique phytochemicals. Thus, they have the potential to become a source of plant-based therapeutic agents. However, many of the them remain uninvestigated. The purpose of this study was to predict the potential of some phytochemicals of the mangrove family as an inhibitor of both viral gene expression and bacterial nucleic acid. Some bioactive compounds of mangrove (taraxerol, pyrethrin, 2-Furancarboxaldehyde, and avicequinone A) were used as subject of this study. The main protease (Mpro) of SARS-Cov-2 virus (PDB ID: 6y2e), the staphylococcus aureus's proteins: topoisomerase II DNA gyrase (PDB id: 2XCT), and tyrosyl-tRNA synthetase (PDB id: 1JIJ) were used as targeted protein. The drug-likeness of compounds were analyzed using Swiss ADME based on the Lipinsky rule of five. Meanwhile, the affinity value between proteins and ligands was predicted using Autodock Vina. The root means square distance (RMSD) value (<2 A) and the binding cavity of drugs (ivermectin and ciprofloxacin) were used as validation parameters. This study resulted that only taraxerol compounds have a violation of Lipinsky's rule. Even so, out of the phytochemical compound of mangrove, the taraxerol has the highest affinity in Mpro and topoisomerase II DNA gyrase protein, although still lesser than ivermectin against Mpro; while avicequinone A has the highest affinity against tyrosyl-tRNA synthetase. This concludes that some phytochemicals of the mangrove family could be developed as an antibacterial and antiviral agents of therapy.